Change Lives in the Poetry of Its Meaning - Bishop, Jay (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper explores three dimensions of change in play therapy. Following the work of Vygotsky, actual case material is used to examine the role of pivots as windows of change in the helping process. It is argued that the pivoting function may serve as a universe for change which allows us to focus more intently on therapeutic events. Doing so gives us questions to address rather than answers to confound.